(3GdehGdi GdhGaOhf Edi eUQ ef GdaJM GdESdGei MJi fgGjI GdOhdI GdENTjOjI21(B-(3358g` (B/ (3642(B-(3969e (B/ s - (3UaGA ZQjH YHOGdYdje NdjaIs; (3MhQjI YHOg YHOGdeLjO SdGe (B: s; (3RfhHI fGOi eQSi CHhRjO (B: s ((3GdbGgQI (B: s (3UaGA ZQjH YHOGdYdje NdjaI (B: s, 2015)
(3jJfGhd gPG GdHMK ehVhY ege ai JGQjN eUQ GdESdGejI jJYdb HOQGSI YfUQ ef GdYfGUQ GdJi dYHJ OhQG h eDKQG ai GdeLJeY GdeUQi h bO JQJH Ydi GSJbQGQge ai eUQ eTGQcJge ai GdMjGI GdSjGSjI h GdGLJeGYjI h GdGbJUGOjI h GdKbGajI HGdGVGaI GddG OhQge ai Gdafhf h GdYeGQI(B. (3h bO CKHJJ GdOQGSI Gf ehbY eUQ GdLZQGai GdgGe cGf CMO CSHGH ONhd GdehGdi Edi CQV eUQ MLGLG Ch JLGQG(B: (3ceG Cf fHhZ YdeGFgG h TjhNgG cGf ef Cge GdCSHGH GdJi OaYJ GdehGdi Gdi GdhahO Gdi eUQ(B: (3h bO JHjf ef GdOQGSI CjVG GdOhQ GdSjGSi GdPi bGe Hg GdehGdi ai eUQ h CjVG ChVGYge GdGLJeGYjI GdeNJdaI HGdEVGaI Gdi OhQge ai Gdafhf h GdYeGQI h eG bGehG Hg ef efTCJ(B: (3ceG HQR YOO cHjQ efge ai cGaI GdYdhes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdJGQjNs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdehGdi s; (3YUQ GdhdGI s; (3eUQs